Linguocultural foundations of neologisms in English and Uzbek internet lexicon - Jalilov , Bahodir Hamzayevich (The Lingua Spectrum, 2026)
This article provides a comprehensive linguocultural analysis of neologisms emerging in English and Uzbek internet lexicon. In particular, it examines the mechanisms of formation of new lexical units under the influence of the global digital communication environment, their semantic transformation, and their functional usage. Internet discourse is characterized by speed, interactivity, and multimodality, and the neologisms formed within it differ from traditional linguistic units by being dynamic and context-dependent.